2004
DOI: 10.1023/b:qure.0000021320.89524.64
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reliability of health-related quality of life measurements among tuberculosis patients

Abstract: The dramatic global impact of tuberculosis on mortality has been well documented, but its impact on morbidity has not been well described. The emphasis on treatment of latent tuberculosis (TB) infection highlights the tradeoff between short-term decrements in health status from 'preventive' therapy, and long-term gains related to fewer cases of active TB. However, these changes in health status have not been characterized. As a first step, we examined the feasibility and reliability of administering two health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(102 citation statements)
references
References 27 publications
2
98
2
Order By: Relevance
“…Another study used normative data from the Canadian population as the reference group and two studies included people with LTBI controls [20,30,39]. The sample size varied among all the studies and only one study reported statistical analysis of sample size [30]. In this review, all kinds of TB patients pulmonary TB, extra pulmonary TB, active TB disease, late TB infection, current TB and recurrent TB were included.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study used normative data from the Canadian population as the reference group and two studies included people with LTBI controls [20,30,39]. The sample size varied among all the studies and only one study reported statistical analysis of sample size [30]. In this review, all kinds of TB patients pulmonary TB, extra pulmonary TB, active TB disease, late TB infection, current TB and recurrent TB were included.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…An article published by Chamla et al [16] described the comparison of TB population group from general population. Another study used normative data from the Canadian population as the reference group and two studies included people with LTBI controls [20,30,39]. The sample size varied among all the studies and only one study reported statistical analysis of sample size [30].…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14 A patient with tuberculosis faces several physiological, psychological, financial and social problems. These problems have a great impact on the well-being of the patient and impair the quality of life of the patient suffering from tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, mental and social well-being as well as physical health are affected by the disease and its related long-termtreatment. 10 Therefore, it is required to investigate the QoL of TB patients to recognize appropriate actions for improvement of health status and the QoL among the patients.…”
Section: Introductionmentioning
confidence: 99%